KECENDERUNGAN PENAMAAN JALAN DI KOTAMADYA DAERAH TINGKAT II SURABAYA - Benny Poerbantanoe (DIMENSI (Journal of Architecture and Built Environment), 1999)
This paper is the result of updating of fact and figures, derived from the draft Master Plan of street names in the IId level municipal area of Surabaya, prepared by the writer when he was making a comparative study in 1996-1997 dealing with result of data drawing and collection from primary sources and secondary sources. It contains an analytical description based on facts, showing the prevaling tendency and pattern of thought in Surabaya, starting from 1706 at a time when the Gemeente of Surabaya was not yet established up to 1998 under the rules of the present IId level municipal governement. In this study is used as yard stick " the theories of urban architecture". Abstract in Bahasa Indonesia : Tulisan ini adalah hasil up-dating dari salah satu bagian konsep Master Plan Nama Jalan di Kotamadya Dati II Surabaya, yang dipersiapkan oleh penulis sewaktu melakukan studi komparasi di antara sigi sekunder dan primer, tahun 1996-1997. Tulisan ini memuat deskripsi analitis yang disusun berdasarkan fakta tentang kecenderungan penamaan jalan serta pola yang berkembang di Kotamadya Daerah Tingkat II Surabaya. Sejak periode pemerintahan pra Gemeente tahun 1706 sampai dengan periode pemerintahan Kotamadya dati II Surabaya tahun 1998, yang dikaitkan dengan teori arsitektur-kota. Kata kunci : nama-nama jalan, surabaya.